'Five goals, no boots': an interrogation of the politics, play and racialised athleticism of late colonial football tours to England, 1949–1959. Issue 4 (2nd October 2018) - Defrates, Lewis
ABSTRACT: This essay explores a series of football tours from Britain's colonies in Africa and the Caribbean to Britain between the years 1949 and 1959. It examines the different desired political and diplomatic functions of the visits from a variety of perspectives, as well as considering the importance of sporting performance and football in particular in fulfilling these functions. Utilising academic work on body cultures as well as critical race theory, it interrogates the coverage and analysis of such tours in multiple outlets of the British media, with particular reference to the different racialisations players from these territories were subject to throughout the period, as well as how racial perceptions were projected, solidified and reconstructed through play and the existing technologies of reception in Britain. Finally, it stresses the importance of localised, seemingly innocuous settings (such as the lower league football stadium) in formulating meaning and signifying identity during the period.